Winter chickpea: status and prospects - Kamel M. (Present status and future prospects of chickpea crop production and improvement in the Mediterranean countries, 1990)
Progress in winter chickpea selection during the last 6 years in Morocco is summarized. Potential yield in regular years is close to 2,0 t/ha for winter chickpea, compared to 0,6 t/ha for spring chickpea. That means a 210 relative gain. Earliness improvement is of 25 to 45 days, depending on planting date and variety. However, the expression of genetic potential is highly influenced by the environment. Certain problems of winter chickpea cultivation as well as research priorities are also discussed in this study.
Present Status and Future Prospects of Chickpea Crop Production and Improvement in the Mediterranean Countries, 11-13 Jul 1988, Zaragoza (Spain)